Utilization of Sludge from Sidoarjo for Synthesis of Microball Photocatalist of Fe2O3 zeolit-chitosan as Fermented Soybean Waste-Degrading Agent - Putri, Erlaningtias Hutami Ardana; Ratnasari, Dwi Fungky; Harumsari, Anugerah Dewi; Lestari, Vivid Ayu; Wardhani, Sri (Jurnal ILMU DASAR, 2016)
The sludge from sidoarjo have high Fe2O3 content of about 62,19%. This content have potential to prepare as photocatalyst for degraded fermented soybean waste by support sunlight. Synthesis of Fe2O3 zeolit-chitosan photocatalyst was carried out by impregnation into zeolite. Adding chitosan into the mixture of Fe2O3 zeolite then cast to be granules. Characterization of photocatalyst obtained using spectrophotometer IR, XRD, and DRS. Microball photocatalyst of Fe2O3 zeolit-chitosan with variation of pH 4, 6, and 8 then were done test of degradation performance by sunlight during 4 hours. As the result, the optimum pH of photocatalyast via COD test is pH 8. The higher base of photocatalyst, decreasing of degradation is higher.Keywords: degradation, Fe2O3, fermented soybean waste, sludge.